Pemberian Zeolit dan Arang Sekam Pada Lahan Sawah Tercemar Limbah Pabrik Terhadap Pb Tanah dan Tanaman Padi - Ester Juliana; Sarifuddin Sarifuddin; Jamilah Jamilah (Universitas Sumatera Utara, 2015)
This study aimed to determine the effect of zeolites and rice husk to soil Pb and growth and production of paddy rice. The research was conducted in the screen house at Faculty of Agriculture USU and soil analyzed at the Laboratory Institute for Agricultural Technology ( BPTP) Medan North Sumatra . This experiment using a factorial randomized block design with two factors , namely zeolite treatment consists of 3 levels: Z0 = 0 g / pot , Z1 = 12.5 g / pot , Z2 = 25 g / pot and rice Husk consists of two levels: A0 = 0 g / pot , A1 = 10 g / pot . The results showed that the rice husk is able to reduce levels of lead (Pb) in the soil while giving zeolite can improve plant height . The interaction between 12.5 g zeolite / pot and 10 g rice husk / pot ( Z2A1 ) increasing weight of 1000 grains . Zeolite and rice husk did not affect significantly for the number of vegetatif and generatif tiller, grain weight per pot and percent of empty grains.Keywords : zeolite , rice husk , Pb , lowland rice